THE ROLE OF TPQ TEACHERS IN OBTAINING PROTECTION AND FULFILLMENT OF RIGHTS AS PROFESSIONALS - Santoso, Dr. Bagus Teguh; Huroiroh, Ernawati; Patrianto, Dr. Bangun; Yuliauriena, Cut Fathiah (Acitya Wisesa: Journal of Multidisciplinary Research, 2024)
Character education and religious teachings are intertwined in shaping Islamic children’s values, with Qur'anic education fostering independence, communication, and piety from an early age. However, Al-Qur'an Education Center (TPQ) teachers, who play a critical role in guiding children's Qur'anic learning, often face challenges due to limited resources, inadequate compensation, and lack of professional development. This research aims to determine how the protection and fulfillment of the rights of TPQ teachers as professionals according to the Job Creation Law, as well as to examine the position of TPQ teachers in Law No. 14/2005 concerning Teachers and Lecturers. This research employs a normative method, primarily using secondary data sources, including both primary and secondary legal materials. The findings of this research revealed that the teaching profession requires professional competence, encompassing roles as educators, mentors, and learning facilitators. Teacher qualifications under Law No. 14/2005 emphasize pedagogical, personality, social, and professional competencies, while protection of teachers’ rights, including legal and work safety guarantees, is essential for their ability to fulfill these responsibilities effectively. Improving TPQ teachers’ professionalism should be prioritized through government-supported training and internal motivation for continuous skill development.